Sisters-in-Waiting: A Case Study of Displaced Syrian Women Fostering New Senses and Memories of Home in Lebanon - Ouaali, Ibtissam; Miedema, Esther (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2023)
Building on variously located Syrian women’s accounts of their day-to-day lives in Lebanon, this article illuminates meaning-making processes in protracted displacement, defined by the UNHCR (2004, p. 1) as a “long-lasting and intractable state of limbo.” We draw on the metaphor of a “constellation of homes” (Brun & Fábos, 2015) to explore various homemaking practices and the interconnected temporal and multi-sensorial dimensions thereof. In so doing, we counter narratives of displaced women as a homogenous collective and problematic assumptions of stasis and passivity associated with protracted displacement. Particular attention is paid to women’s narratives regarding “purposeful work” and, crucially, female friendship, which we argue can be understood as additional nodes in the constellation of homes. We argue that further and different forms of research are required to do justice to the multi-sensorial dimensions of homemaking and the novel concept of “sisters-in-waiting” in the lives of women in protracted displacement.